The Distribution Pattern of Marine Bivalve Death Assemblage From the Western Margin of Bay of Bengal and Its Oceanographic Determinants - Chattopadhyay, Devapriya; Sarkar, Deepjay; Bhattacherjee, Madhura (Frontiers in Marine Science, 2021)
The global pattern of shallow marine biodiversity is constructed primarily using the data from extra-tropical sites. A severe knowledge gap in the shallow benthic diversity exists for the tropical Indian Ocean, especially along the coastline of peninsular India. Latitudinal biodiversity gradient (LBG)—a poleward decrease in diversity, even though accepted as a pervasive global pattern, often differs from regional trends. Although several oceanographic variables are known to influence regional patterns, their relative effect in shaping the shallow benthic community in tropical seas remains unclear. The east coast of India bordering the Bay of Bengal (BoB) presents a 2,500 km stretch (8–22°N) of tropical coastline with a spatial variation in oceanographic parameters including freshwater mixing, primary productivity, temperature, and shelf area. Here, we documented the marine bivalve distribution using spatially-temporally averaged beach samples and evaluated their relationship with the oceanographic variables. Our data reveal the existence of a highly diverse fauna, comparable to other tropical shallow marine sites. Overall species composition reflects a typical assemblage of the Indian Ocean, dominated by Veneridae but shows an uncharacteristically low proportion of Tellinidae and Lucinidae. The latitudinal variation in diversity shows a mid-latitude drop at around 14°N—a pattern inconsistent with the prediction of latitudinal biodiversity gradient (LBG). The functional groups are dominated by infauna (65%), unattached groups (69%), and suspension feeders (87%). There is only a slight difference in species composition between southern and the northern sites pointing to a predominantly continuous circulation and considerable mixing within the BoB. Productivity range, shelf area, and salinity emerge as best predictors of the species richness. All environmental variables together explain the species composition across the latitudinal bins satisfactorily. The species composition of the east coast shows no distinct nature in comparison to the Indo-Malayan biodiversity hotspot; the proximity to this hotspot and biological exchange with it may have contributed to the high diversity of the east coast fauna. Our study highlights the complex interplay between multiple oceanographic variables in determining the distribution and diversity of tropical shallow marine benthos at a regional scale generating biodiversity patterns that are at odds with global trends such as LBG.